Furosemide for prevention of cyclophosphamide‐associated sterile haemorrhagic cystitis in dogs receiving metronomic low‐dose oral cyclophosphamide. (14th February 2017) - Setyo, L.; Ma, M.; Bunn, T.; Wyatt, K.; Wang, P.
Abstract: Sterile haemorrhagic cystitis (SHC) is a known risk of cyclophosphamide treatment. Diuresis using furosemide is effective in canines when maximally tolerated dosed cyclophosphamide is administered. This retrospective study aimed to determine whether orally administered furosemide decreased the incidence of SHC. Secondary aims were to identify predisposing factors for SHC. One‐hundred and fifteen dogs treated with metronomic cyclophosphamide were analysed retrospectively. Populations were not randomized. 25 dogs (21.7%) developed SHC. Furosemide administration significantly reduced the likelihood of SHC development ( P = 0.010, where SHC was diagnosed in 30.3% of dogs administered cyclophosphamide without furosemide, and 10.2% of dogs administered cyclophosphamide with furosemide). Age, gender, breed, bodyweight, number of cyclophosphamide treatments, piroxicam use and previous or pre‐existing disease were not found to be associated with SHC development. This study demonstrates furosemide is effective in the prevention of SHC and its use may be considered when implementing metronomic cyclophosphamide therapy.